Evaluation of The Intrusion Forces Created by Burstone Intrusion Arches Manufactured with Two Different Designs - An Invitro Study - كلش سعيد; جمال دباس (Latakia University Journal -Medical Sciences Series, 2023)
The aim of study: The current study aimed to look at the relationship between the design of intrusion arches and the resulting force. Materials and Methods: We used stainless steel wires with sections of 0.016 x 0.022 inch and 0.017 x 0.025 inch to make two different models of Burstone intrusion arches, the first group was designed by making a V-shaped bend and the second group was designed by making a Helix loop each sample consisted of 10 wires per section used. The resulting force was recorded at activation distances of 5-10-15-20 mm. Results: All recorded forces had a significant difference between the two designs when compared, and in this study, the significant force difference was confirmed between each of the activation distances of 5, 10, 15, and 20 mm for each of the two analyzed designs, and a significant difference was obtained in the resulting force when using two different sections. Thus, the current study showed the importance of choosing the design and section of the intrusion arches used, as it recorded two different values of force - almost half of the amount of force in the Burstone arches with a loop - when using either design at any degree of activation. The force resulting from Burstone arches without a loop is high, especially when using section 0.017 x 0.025 inch.